Numerical Simulation on Cement Hydration and Microstructure Development in Repair-Substrate Interface - Lan, Mingzhang; Zhou, Jian; Li, Hui; Wang, Ying (Frontiers in Materials, 2022)
One of the key parameters for the performance of concrete repairs is the quality of the interface between the repair material and concrete substrate, which is determined by cement hydration and microstructure development. The moisture exchange between the repair material and concrete substrate plays an important role in the cement hydration and porosity of cementitious repair materials. To better understand the influence of moisture exchange on the hydration of cementitious repair materials, this paper presents a numerical simulation of cement hydration and microstructure development of repair materials, considering moisture exchange. The simulation results reveal that the moisture exchange between the repair material and concrete substrate results in a water content change in two parts. Before the repair material setting, the water absorption of an unsaturated concrete substrate causes a reduction in the w/c ratio in the repair material, decreasing the hydration rate of the repair material. After the repair material setting, the water migrates from the concrete substrate to the repair material to provide additional water to accelerate the hydration of unhydrated cement in the repair material.